INFORMASI KEBAKARAN HUTAN DAN LAHAN BERDASARKAN INDEKS KEKERINGAN DAN TITIK PANAS DI KABUPATEN SAMOSIR - Pardamean Abadi; Rahmawaty Rahmawaty; Yunus Afifuddin (Program studi Kehutanan USU, 2013)
Samosir District is one of the very prone to forest fire and land. This study aimed to determine the level of fire danger in forest and land use data Samosir regency with the maximum temperature, rainfall and hot spots daily, monthly and yearly 2009, 2010 and 2011. Data analysis was performed at the Laboratory of the Faculty of Forest Inventory Forestry Department of Agriculture using exel Spreadsheet software and Arc. View 3.3. The number of hot spots are detected and the high drought index obtained occur when rainfall is low and did not even rain. Low rainfall occurred in March-July, so in the many forest fires and land. While high rainfall occurred in August-February. Hot spots and drought indices can be used together as an early warning system for the prevention of fire and forest fire management and land on Samosir District. The research showed that the level of the fire crisis in Samosir Regency tend to to lower where fire was only became of the certain months during the year that is during the month of Maret-Juli. The prediction of fire Danger in Regency of Samosir be at the month of Maret-Juli, where very low rainfall value so that assess the high KBDI with the value make an index to the dryness be at the scale high-extreme that it’s among 1500-1749 and 1750-2000 Keywords : Forest and Land Fire Information, fire crisis, Dryness Index, Hotspot